GOOD INTENTION ON ELECTRONIC CONTRACT THROUGH E-COMMERCE - Ari Purwadi (Jurnal Dinamika Hukum, 2015)
Electronic contract (e-contract) is a contract that vulnerable to the emersion of problems because the contract happened between absence persons. This problem can be avoided if businessman who included in the electronic commerce using principle of good intention. According to the Information and Electronic Transactions Act declare that good intention shall be given during the transaction taking place, it must be interpreted both in the pre-transaction stage, transaction stage, and post-transaction phase. Thus, in order to protect consumer, it's good intention should be exist in every phase of consumer transaction. Keywords: Electronic Contract, Good Intention, Consumer Transaction.